Both biotic and abiotic factors influence floral longevity in three species of Epidendrum (Orchidaceae). Issue 3 (2nd April 2014) - Vega, Yesenia; Marques, Isabel
Abstract Extended flower longevity has been widely defended to occur as a consequence of low pollination activity. To test this hypothesis in Neotropical rainforests, we selected three species of Epidendrum that flower during rainy conditions and commonly exhibit low levels of insect visits. Experimental studies carried out in 15 populations distributed along a wide spatial gradient detected the presence of pollinator limitation in all populations. Pollinia removal without pollen deposition increased longevity, and thus extended longevity could apparently be considered as an ecological advantage for these orchids. Nevertheless, flower longevity was severely shortened by abiotic factors like precipitation and humidity. Comparison with other tropical orchids showed that flower longevity was higher even in species that flower during periods of more pollinator activity than the ones studied here, which is contrary to the hypothesis that pollinators are the only driving force for long‐lived flowers in Epidendrum. Thus, although long floral longevities are apparently favorable for the reproductive success of these species, the high maintenance costs experienced during rainy conditions are also an important factor constraining the selection of long‐lived flowers in Epidendrum.